2022
DOI: 10.1525/elementa.2021.00092
|View full text |Cite
|
Sign up to set email alerts
|

CH4 isotopic signatures of emissions from oil and gas extraction sites in Romania

Abstract: Thallium (Tl) is a highly toxic trace metal widely distributed in water environments, which may threaten the water quality and aquatic organisms at excessive levels due to increased anthropogenic activities. This study investigated the changes in microbial communities of intestines and organs of zebrafish. The toxic response assessments include intestinal microbiota composition and the histopathology of zebrafish’s gill and liver tissues under exposure of Tl at environmental-relevant levels. The results suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 98 publications
1
11
0
Order By: Relevance
“…Some species in Mycobacterium have been reported to enhance the immunity in aquatic species like salmonids without any negative effects (Prathiviraj et al, 2021). However, several studies indicated that Mycobacterium might be a potential opportunistic pathogen to cause chronic long-term persistent infections in the gut of zebra fish (Wang et al, 2021;Wu et al, 2021). In our study, the relative The Israeli Journal of Aquaculture -Bamidgeh • IJA.73.2021.1520998 abundance of Mycobacterium was higher in CAs group, while no intestine health problem was observed during the cultivation process.…”
Section: Discussionmentioning
confidence: 41%
“…Some species in Mycobacterium have been reported to enhance the immunity in aquatic species like salmonids without any negative effects (Prathiviraj et al, 2021). However, several studies indicated that Mycobacterium might be a potential opportunistic pathogen to cause chronic long-term persistent infections in the gut of zebra fish (Wang et al, 2021;Wu et al, 2021). In our study, the relative The Israeli Journal of Aquaculture -Bamidgeh • IJA.73.2021.1520998 abundance of Mycobacterium was higher in CAs group, while no intestine health problem was observed during the cultivation process.…”
Section: Discussionmentioning
confidence: 41%
“…A CRDS instrument (G4302, Picarro Inc., USA) was installed in the aircraft, and samples were taken from the outflow of the instrument into bags of 2 L (Supel™-Inert Multi-Layer Foil bags, Sigma-Aldrich Co. LLC, USA) when an increase in CH 4 mole fractions was observed. The method is described in detail in Menoud et al (2022b).…”
Section: Samplingmentioning
confidence: 99%
“…2. The fossil fuel sources partly overlap with the range of thermogenic CH 4 , but also spread towards lower δ 13 C or higher δ 2 H. This is due to the presence of natural gas of microbial origin in the coal reservoirs of Silesia, in Poland (Kotarba, 2001;Kotarba and Pluta, 2009;, and in Romania (Baciu et al, 2018;Fernandez et al, 2022;Menoud et al, 2022b). We concluded that this microbial CH 4 originates from the CO 2 reduction pathway as defined by Milkov and Etiope (2018), with relatively depleted δ 13 C (< −60 ‰) and relatively enriched δ 2 H (> −250 ‰).…”
Section: The European Methane Isotope Database (Emid)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tl is present in the soil in very small amounts; i.e., less than 1 mg/kg [10,12,13], but it is reported to be highly toxic [14][15][16] even more toxic than Hg, Cd, Pb, Cu, and Zn [17,18]. The range of Tl detection in areas of pyrite deposits was from 5 to 15 mg/kg, and near sulfide deposits was from 40 to 124 mg/kg [19][20][21].…”
Section: Introductionmentioning
confidence: 99%